High temperature polymer blends - DeMeuse, Mark T. (Woodhead Publishing, 2014)
Annotation Polymer blends offer properties beyond those of single polymers and provide the opportunity to tailor and control properties through selection of the blend composition. An important area for polymer blends is high temperature applications where existing polymers could not normally be used. This book reviews recent research in the field, including characterisation methods and analysis of the thermodynamic properties of these blends. It also reviews the use of materials such as liquid crystals as reinforcements as well as applications in such areas as energy and aerospace engineering.
Keywords: Polymers -- Thermal properties.; elektronické knihy; electronic books